Reflections From Co-Researchers With Intellectual Disability: Benefits to Inclusion in a Research Study Team - St. John, Brittany (Intellect Dev Disabil, 2018)
Participatory action research methodologies may empower and protect marginalized individuals; however, they remain underutilized. Limited studies have investigated the impact of participatory action research, specifically on individuals with intellectual disability (ID). This study examines (1) the perspectives of co-researchers with ID on their involvement in the research process and (2) the feasibility of their inclusion based on perspectives of research staff (academic faculty and graduate students without ID). Three co-researchers with ID were interviewed regarding their research participation. Thematic analysis of interviews identified four themes: (1) Shared Experience of Disability, (2) Teaching and Guidance, (3) Acquisition of Skills and Knowledge, and (4) Value of Participation. Research staff reviewed field notes and identified benefits and challenges to feasibility of including co-researchers with ID. Inclusion of co-researchers with ID was found to be both meaningful and feasible.